Implementation of Digital Twin for Investigation of Delayed Building Construction - Muhammad Rizal Mutaqien,; Nurpusparatnasaridewi,; Astor, Yackob; Moch. Imam Muflih,; Pratama, Dandi Haniif; Ananda Amatory Zahra,; Yasuyuki Nabeshima, (International Journal of Integrated Engineering, 2025)
During 2020-2022, a significant portion of the national budget was redirected to the healthcare sector for the handling of COVID-19 and economic recovery in Indonesia. This policy has resulted in delays in infrastructure development both nationally and locally. One example is the construction of a government office in Bandung. If construction resumes, investigating the level of damage to structural elements becomes crucial. In this research, the investigation of the level of damage was conducted by constructing a Digital Twin in the form of a 3D building model using the Terrestrial Lasser Scanner (TLS) BLK360, Cyclone Register 360 software, and Autodesk Recap Pro. The visual investigation results on the 3D model show the presence of 31 elements, with 39% mild damage and 61% moderate damage out of the total detected damage on columns, beams, and slabs. On the structural element, tests were conducted, with the assistance of the Non-Destructive Test (NDT) equipment, and the examination of the nominal moment capacity strength of the structural elements showed that several elements have experienced damage and a reduction in nominal moment capacity after 3 years construction delayed. On the column there was an increase in nominal moment capacity by 47 kNm and shear strength difference of 5.394 kN. On the Beam, there was a decrease in negative nominal moment capacity, where the value of M_(n^- ) actual = 187,067 kNm while the M_(n^- ) planned = 241,389 kNm. On floor slab there was a decrease in the nominal moment capacity in the x-direction M_n actual = 22,984 kNm while the M_n planned = 28,932 kNm. In the y-direction M_n actual = 24,167 kNm while the M_n planned = 22,594 kNm. Based on the investigation results, the delayed building construction can be resumed by repairing and strengthening the damaged structural elements using grouting, epoxy injection, and Fiber-Reinforced Plastic (FRP) methods.